Continuing effects of early enrichment in adult life: The Turkish Early Enrichment Project 22 years later - Kagitcibasi, Cigdem; Sunar, Diane; Bekman, Sevda; Baydar, Nazli; Cemalcilar, Zeynep (Elsevier Science Inc, 2009)
Long-term Studies of early intervention, spanning over decades, are scarce in the United States and nonexistent in the rest of the world. The Turkish Early Enrichment Project (TEEP) is the only non-U.S. example to date. This paper reports a new follow-up assessment of the long-term outcomes of TEEP, an intervention carried out in 1983-1985 with 4-6 year old children from deprived backgrounds (previous evaluations were carried out at the completion of the intervention and seven years later). Findings from 131 of the original 255 participants indicate more favorable outcomes for children who received either mother training or educational preschool, or both, compared to those who had neither, in terms of educational attainment. occupational status, age of beginning gainful employment, and some indicators of integration into modern urban life, such as owning a computer. Further analyses of the intervention effects on the complete post-intervention developmental trajectories indicated that children whose cognitive deficits prior to the intervention were mild to moderate but not severe benefited from early enrichment. Thus, a majority of the children who received early enrichment had more favorable trajectories of development into young adulthood in the cognitive/achievement and social developmental domains than comparable children who did not receive enrichment. (C) 2009 Elsevier Inc. Ail rights reserved.
Keywords: Early Enrichment; Preschool Education; Mother Training; Long-Term Effects; Early Childhood İntervention; Early-Childhood Intervention; United-States; Income; Home; Children; Program; School